CARTOON VISUALIZATION AS SOCIAL REPRESENTATION IN BOG-BOG BALI CARTOON MAGAZINE 2011/2012 EDITION - Swandi, I Wayan; Wirawan, AA Bagus; Artayasa, I Nyoman; Mudana, I Gede (E-Journal of Cultural Studies; Volume 9, Number 4, November 2016, 2016)
Bog-Bog cartoon was a mass media production which was rich in strong artistic and Balinese cultural values. Social changes cannot be avoided since Bali became a global tourist destination. On one hand, Bali cannot be avoided from being attracted by the global strength; on the other hand, attempts are perpetually made to maintain its cultural identity. The descriptive method was used in the present study, which was intended to explain how the Bog-Bog cartoon was visualized and what meanings were hidden in it.
Keywords: Visualization, Cartoon, Bog-Bog Magazine, Social Representation